Comparison of the mechanisms of nongenomic actions of thyroid hormone and steroid hormones - Davis, Paul J.; Tillmann, Hanns-Christian; Davis, F. B.; Wehling, Martin (Journal of endocrinological investigation, 2002)
Steroids and thyroid hormone are thought primarily to act via binding to hormonespecific nuclear receptor superfamily members. The nuclear ligand-receptor complexes then initiate transcriptional activity. Actions of steroids and iodothyronines that are nongenomic or extranuclear in mechanism have been recognized recently and new insights into such mechanisms are available. Despite their distinct structures and biologic effects, the two families of hormones have similarities in the mechanisms of their nongenomic actions. That is, both steroids and thyroid hormone appear to interact with specific cell surface G protein-coupled receptors and to activate signal transducing kinases such as those involved in the mitogen-activated protein kinase (MAPK) pathway. Much is known about the ability of certain steroids such as estrogen and mineralocorticoids to increase [Ca2+]i acutely and stimulation of the MAPK cascade by L-T4 appears to depend upon a hormone-induced increase in [Ca2+]i via phosphoinositide pathway activation. At least in the case of iodothyronines, hormone activation of the MAPK pathway modulates the cellular activities of certain cytokines and growth factors. One of the two cell surface estrogen receptors (ERs) may be an expression of the same transcript as that for nuclear ER, whereas the mineralocorticoid and progesteronebinding proteins in the plasma membrane appear to be products of genes different from those of nuclear receptors. Iodothyronine structure-activity relationships at the plasma membrane binding site for thyroid hormone suggest that the cell surface receptor for T4 that also binds 3,5,3′-triiodo-L-T3 is different from the nuclear T3 receptor (TR). There are interfaces of nongenomic and genomic mechanisms for both steroids and thyroid hormone. For example, by nongenomic mechanisms, estrogen and thyroid hormone can promote serine phosphorylation, respectively, of nuclear ER and TR. Transcriptional activity of the nuclear receptor proteins can be altered by such phosphorylation.
Elektronische Reproduktion der Druck-Ausgabe 11 März 2014
Gesehen am 10.08.2022